2015
DOI: 10.1093/cercor/bhv026
|View full text |Cite
|
Sign up to set email alerts
|

Altered Structural Brain Networks in Tuberous Sclerosis Complex

Abstract: Tuberous sclerosis complex (TSC) is characterized by benign hamartomas in multiple organs including the brain and its clinical phenotypes may be associated with abnormal neural connections. We aimed to provide the first detailed findings on disrupted structural brain networks in TSC patients. Structural whole-brain connectivity maps were constructed using structural and diffusion MRI in 20 TSC (age range: 3-24 years) and 20 typically developing (TD; 3-23 years) subjects. We assessed global (short- and long-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 77 publications
3
35
0
Order By: Relevance
“…Conversely, disorders of white matter are associated with disruptions in alpha oscillations, with decreased PAF demonstrated in vascular dementia [Moretti et al, 2004], multiple sclerosis [Leocani et al, 2000;Tewarie et al, 2014;Van der Meer et al, 2013], and white (but not gray) matter tumors [Gloor, Kalabay, & Giard, 1968;Goldensohn, 1979]. Decreased PAF and reduced APC may therefore indicate delayed or atypical maturation of white matter during the infancy period, which is consistent with the disrupted interhemispheric white matter connections that have been identified later in TSC [Baumer et al, 2017;Im et al, 2016;Krishnan et al, 2010;Peters et al, 2012].…”
Section: Tsc/td Group Comparisonmentioning
confidence: 83%
See 2 more Smart Citations
“…Conversely, disorders of white matter are associated with disruptions in alpha oscillations, with decreased PAF demonstrated in vascular dementia [Moretti et al, 2004], multiple sclerosis [Leocani et al, 2000;Tewarie et al, 2014;Van der Meer et al, 2013], and white (but not gray) matter tumors [Gloor, Kalabay, & Giard, 1968;Goldensohn, 1979]. Decreased PAF and reduced APC may therefore indicate delayed or atypical maturation of white matter during the infancy period, which is consistent with the disrupted interhemispheric white matter connections that have been identified later in TSC [Baumer et al, 2017;Im et al, 2016;Krishnan et al, 2010;Peters et al, 2012].…”
Section: Tsc/td Group Comparisonmentioning
confidence: 83%
“…Many infants with TSC show developmental delays and emerging signs of ASD by 12 months of age, with the most robust differences occurring between 12 and 24 months of age [Capal et al, 2017;Jeste et al, 2014;McDonald et al, 2017]. Recent evidence from older children and adults with TSC suggests that widespread alterations in neural connectivity are associated with the presence of neurodevelopmental disorders in TSC [Im et al, 2016;Lewis et al, 2012;Peters et al, 2012Peters et al, , 2013. Here, we report differences in network disruption (quantified using EEG measures of PAF and APC) across a clinically representative (high incidence of epilepsy and associated medications as well as cortical tuber burden) cohort of participants with TSC, thus reinforcing the value of these EEG biomarkers even in the context of extensive clinical comorbidities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to better disentangle the exact timing and mechanism of these earliest signs of atypical development in TSC, we need to investigate the neural and genetic mechanisms that underlie these early behavioral deficits. These studies must be rooted in the examination of neural circuitry, as both preclinical and clinical studies of TSC confirm aberrant long range and local neural connectivity, abnormal axon guidance, and delayed myelination in TSC [Im et al, ; Krishnan et al, ; Makki, Chugani, Janisse, & Chugani, ; Meikle et al, ; Peters et al, ; Nie et al, ]. Large scale imaging studies in high‐risk siblings have shown that early disruptions in brain development precede atypical behaviors, with findings demonstrating differences in basic processes such as long range connections, functional connectivity, corpus callosum volume and structure, and cortical surface volume [Emerson et al, ; Hazlett et al, ; Wolff et al, , ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, structural imaging studies in individuals with TSC demonstrate widespread alterations in structural connections (Baumer et al, 2015;Krishnan et al, 2010;Lewis et al, 2012;Peters et al, 2012Peters et al, , 2012, relevant to the variability seen in neurodevelopmental outcomes. Using an unbiased whole-brain connectivity analysis, Im et al (2016) identified altered structural connectivity in TSC with markedly reduced inter-hemispheric connectivity (aged 3-24 years) compared to a control sample, most prominent in those with developmental delay (Im et al, 2015). Similarly, deficits in the integrity of white matter microstructure are found to be more pronounced in individuals with TSC who also have an ASD diagnosis (Baumer et al, 2017;Lewis et al, 2012;Peters et al, 2012).…”
Section: Introductionmentioning
confidence: 99%